THE DIRECT EFFECT OF THE LEADERSHIP ON THE SERVICE PERFORMANCE AND THE INDIRECT EFFECT THROUGH THE JOB STATISFACTION, ORGANIZATIONAL COMMITMENT, ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Rini Larono, Stenly; Jawali Jurry Ektivianus (Dinasti International Journal of Economics, Finance & Accounting, 2020)
The aims of the research is to determine the direction and the extent of the hospital leadership on job satisfaction, organizational commitment, organizational citizenship behavior and employee service performance at the type C regency general hospital of the Talaud isles regency, north Sulawesi province. The research employed the civil servant employee working at the hospital H. also employed a survey sampling technique with structural questionnaires, using a liker type scale with five ranks. The data of 130 civil seruan employee respondents was the collected from type C regency general hospital of Talaud isles regency analyzed with structural equation Model (SEM) analysis with Amos 22.0 version and SPPS program of 22.00 version. The result and the findings of the research indicated that there is an indirect, positive and significant influence of hospital leadership on employee service performance through job satisfaction and organizational citizenship behavior.